2007 16th IST Mobile and Wireless Communications Summit 2007
DOI: 10.1109/istmwc.2007.4299166
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Measurements supporting Reconfiguration in Heterogeneous Networks

Abstract: Abstract-This paper represents spectrum occupation measurements performed during the Soccer World Cup 2006 in Germany. The measurements cover the range from 400 MHz up to 2600 MHz including among other communication standards GSM 900, DCS 1800, UMTS, and WiFi. The intention of the paper is to compare spectrum occupation during a mega-event to spectrum allocation in a "normal usage" situation and to investigate correlation between the received power levels and specific events, e.g., scoring within a match. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For example, the spatial distribution of the spectral occupancy was analyzed in [241] in the context of a cellular mobile communication system. In contrast to other similar works where a cellular network is monitored from outside the system by means of field measurements and in a limited geographical region [167,168,277], the study reported in [241] monitors the arrival of calls from inside the system and over hundreds of base stations simultaneously in the period of three weeks. Based on such measurements and making use of variograms, the study presented in [241] analyzes the spatial variability of the spectral occupancy for sectors of the same and different cells as well as the correlation among various cells based on the traffic supported during the minute of maximum load.…”
Section: Previous Workmentioning
confidence: 96%
“…For example, the spatial distribution of the spectral occupancy was analyzed in [241] in the context of a cellular mobile communication system. In contrast to other similar works where a cellular network is monitored from outside the system by means of field measurements and in a limited geographical region [167,168,277], the study reported in [241] monitors the arrival of calls from inside the system and over hundreds of base stations simultaneously in the period of three weeks. Based on such measurements and making use of variograms, the study presented in [241] analyzes the spatial variability of the spectral occupancy for sectors of the same and different cells as well as the correlation among various cells based on the traffic supported during the minute of maximum load.…”
Section: Previous Workmentioning
confidence: 96%
“…Measurements are used in Reichl et al 16 for investigating the transmission control protocol/internet protocol (TCP/IP) performance of an integrated UMTS/GPRS/ wireless fidelity (WiFi) network. Renk et al 17 also use measurements for analyzing the impact of big sport events on the performance of an integrated UMTS/ GPRS/WiFi network.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some large-scale measurement-driven characterizations of the PU activities in cellular networks are also carried out for different spectrum bands. In [9], the authors analyze the spectrum occupancy of PUs in GSM and UMTS bands. In [10], the PU activities are analyzed in the New York cellular bands, i.e., CDMA and GSM.…”
mentioning
confidence: 99%